2006
DOI: 10.1111/j.1365-2044.2006.04749.x
|View full text |Cite
|
Sign up to set email alerts
|

On‐call stress among Finnish anaesthetists*

Abstract: SummaryWe investigated on-call stress and its consequences among anaesthetists. A questionnaire was sent to all working Finnish anaesthetists (n = 550), with a response rate of 60%. Four categories of on-call workload and a sum variable of stress symptoms were formed. The anaesthetists had the greatest on-call workload among Finnish physicians. In our sample, 68% felt stressed during the study. The most important causes of stress were work and combining work with family. The study showed a positive correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 45 publications
5
93
0
7
Order By: Relevance
“…at nights and at weekends). The findings echo those of an earlier study in Finland [29]. A survey in New Zealand reported that a substantial proportion of anaesthetists believed their weekly work hours jeopardised both patient safety and their own wellbeing [30].…”
supporting
confidence: 82%
“…at nights and at weekends). The findings echo those of an earlier study in Finland [29]. A survey in New Zealand reported that a substantial proportion of anaesthetists believed their weekly work hours jeopardised both patient safety and their own wellbeing [30].…”
supporting
confidence: 82%
“…Moreover, the Taiwanese study reported a higher proportion of persons suffering from depression among physicians than in the general population (13.3% vs. 3.7%). In a study investigating on-call workload among Finnish anesthetists, a total of 68% felt stressed [14]. Certain specialists such as surgeons are more stressed than others [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…The work demands of some shift worker occupations may also be especially stressful due to the special nature of the work (eg, on-call emergency work and working alone). For example, 68% of a representative group of anesthetists reported stress, and 18% had moderate burnout (75). Being frequently oncall had a dose-response type relationship to the existence of stress symptoms, burnout, and feelings of exhaustion.…”
Section: Shift Workmentioning
confidence: 97%